Clinical outcomes of hospitalized patients with chikungunya fever: A retrospective analysis - Lucas Lobo Mesquita; Ênio Simas Macedo; Sérgio Luiz Arruda Parente Filho; Francisca Lillyan Christyan Nunes Beserra; Evelyne Santana Girão; Juliana Mandato Ferragut; Roberto da Justa Pires Neto; Geraldo Bezerra da Silva Júnior; Elizabeth De Francesco Daher (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To describe the prognostic and clinical profile of hospitalized patients with chikungunya virus (CHIKV) infection focusing on renal outcomes. Methods: This is a cross-sectional study including all patients with confirmed chikungunya fever (CHIKF) admitted to 3 different high-complexity hospitals in Fortaleza, Brazil between January 2016 and June 2017. Data analysis was carried out to evaluate correlation between clinical profile and outcomes. Results: Fifty-five patients were included, with a median age of 77 (IQR=21) years, and 23 (41.82%) were male. Twenty-five patients (45.45%, 25/55) developed acute kidney injury (AKI), and 15 (60.00%, 15/25) were classified as KDIGO 1, 1 (4.00%) as KDIGO 2, and 9 (36.00%) as KDIGO 3. The overall mortality was 34.54% whilst AKI-related mortality was 64.00% (16/25). Both AKI and encephalitis were associated with higher mortality. Patients who died were significantly older [82 (IQR=12) years vs. 70 (IQR= 28.75) years, P<0.001)]. In the multivariate analysis, abdominal pain was associated with an increased risk of severe AKI (OR=5.33, 95% CI=1.11–25.64, P=0.037) and AKI was an independent risk factor of death (OR=12.06, 95% CI=2.55–57.15, P=0.002). Recovery of renal function was similar among the different age groups. Conclusions: AKI is present in half of the study population and is an independent risk factor of death. Thus, renal function should be carefully monitored in hospitalized patients with CHIKV infection.